Diagnóstico y tratamiento pediátricos - Levin, Myron J.; Abzug, Mark J.; Maya, Bunik; Hay, William W., Jr (McGraw-Hill's AccessMedicina., 2020)
The twenty-fifth edition of Pediatric Diagnosis and Treatment presents practical, updated and well-referenced information on the care of children from birth to lactation and adolescence. Pediatric diagnosis and treatment emphasizes the clinical aspects of pediatric care while covering important underlying principles. The book provides an excellent guide to the diagnosis, understanding, and treatment of medical problems for all pediatric patients, in an easy to use and read format.